Integration and embedding of vital signs sensors and other devices into textiles - Abreu, Maria José Araújo Marques (2010)
The development of ubiquitous vital sign monitoring has become a very up-to-date research theme for many academics and industrial companies in the last years. With new materials and integration techniques, it is possible to implement vital sign monitoring in an economic manner, directly into textile products. This unobtrusive presence of sensors is especially important for the monitoring of children or elderly people. This paper focuses on two aspects of sensor integration: Integration of off-the-shelf electronic components, and the use of the textile material itself as sensor, or in general as an electrically active element presenting some exploratory work in the integration of electronic devices into textiles. The main objective was to reproduce and improve on previous work presented by other authors, and foster possibilities of developing garments for vital sign monitoring with immediate industrial and economic feasibility. The use of standard production techniques to produce textile-based sensors, easily integrated into garments and with mass-market potential, is one of the important motivations for this work.